Tinjauan Implikasi Hukum Terhadap Penagihan Hutang Melalui Media Sosial - Siska Yulia Chandra Eyato; Nur Mohamad Kasim; Sri Nanang Meiske Kamba (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
This research aims to determine the legal implications of debt collection via social media. This research is normative research with a conceptual approach, which is analyzed descriptively qualitatively. The results of the research show that the legal implications of debt collection from an agreement as fulfillment of performance are viewed from article 1365 of the Civil Code, every act that violates the law and brings loss to another person, requires the person who caused the loss through his fault to compensate for the loss, giving meaning in principle in debt and receivable agreement that has been agreed, if the agreement cannot be implemented by one of the parties then an unlawful act has occurred. In fact, debt collection via social media is not a violation as long as it does not lead to defamation of the debtor. There is a difference between unlawful acts in the context of criminal law and unlawful acts in the context of civil law, namely that more emphasis is placed on the differences in the nature of criminal law which is public in nature and civil law which is private in nature.